Development of TEC measurement and calculation module: conversion process from TECs to TECv / Mohd Naqiuddin Mohammed - Mohammed, Mohd Naqiuddin (2009)
The dual frequency global positioning system (GPS) acts as an effective tool used to investigate the earth's atmospheric layers. Through a linear combination of GPS range and phase measurements observed on two carrier frequencies (LI and L2) by terrestrial based GPS receivers, the ionospheric total electron content (TEC) along oblique GPS signal paths may be quantified. This is why it is imperative to calculate the value of TECv. The TECv are more accurate than TECs due to the fact that the signals travel much lesser thus less propagation error. In this paper efforts are made to examine how the TECs is calculated and its conversion process to TECv from the RINEX file containing the GPS data. These values are than analyzed to find the significance of the elevation angle in the difference of the TECs and TECv values. The difference of the TEC readings in this paper was also tabulated to see the difference in the TEC values between the day and night time. This paper investigates the TEC covering the period of 10th of July 2006 and 8th of November 2005 in two different periods of time (day and night) in the same time interval of two hours using the data from receiver stations located at Universiti Sains Malaysia, Penang and Wisma Tanah Kuala Lumpur, KTPK respectively. Different satellite PRN tracks are chosen to obtain data with the best elevation angle. This is vital in order for this paper to calculate accurate TEC data.